(untitled) (Research, Society and Development, 2021)
Objective: The main objective of the study is to understand how the criminalization of abortion in Brazil has consequences for public health, from the perspective of the literature. Knowing that, even though abortion is a crime in our country, it is carried out in a way that endangers the lives of thousands of women. This implies high costs to the health system, damage to individual reproductive health and the death of women. Methodology: This work is an integrative literature review carried out in the SciELO, LILACS, MEDILINE and Pubmed libraries and databases, for the last ten years (2010-2020), in Portuguese, English and Spanish. Results: Of the 6 studies selected for the final sample. It appears that abortion-related maternal mortality is considered a public health problem, although abortion is considered a crime in the country, such restriction does not prevent women from giving up this practice. Thus, they look for means of clandestine procedures, the illegal termination of pregnancy can have negative consequences for the woman or even lead to death. Final Considerations: In Brazil, abortion involves socioeconomic factors, as the wide range of women who die without economic resources is of greater percentage, compared to those privileged with a higher economic and social level. Thus, there is no way to eradicate abortion in Brazil, but a plan to welcome these women into the Unified Health System (SUS).